Skin sensory alteration and kneeling ability following cruciate retaining total knee arthroplasty are not affected by the incision position: A randomised controlled trial of simultaneous bilateral surgery - Sergio Barroso Rosa; Matthew Wilkinson; Peter McEwen; Levi Morse; Andrea Grant; Kenji Doma; Charles Haward; Matthew Rikard‐Bell (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose The purpose of this randomised controlled trial was to assess the impact of skin incision location on the patients’ ability to kneel. Methods A total of 29 patients undergoing bilateral total knee arthroplasty (58 knees) were randomised to receive a lateral or midline incision, with the contralateral limb receiving the alternative option. Cruciate retaining implants were used in all cases by three experienced arthroplasty surgeons. The primary outcome measures assessed functional ability to kneel using an innovative five‐point kneeling scale, preferred knee to kneel on and the area of cutaneous sensory loss around the incision at 6 weeks, 6 months and 12 months. Secondary outcome measures were the OKS, KOOS JR, FJS and EQ5D patient reported outcome measures (PROMS), length of surgical scar, overall knee preference and range of motion (ROM). Results There were no significant differences between the two groups for any primary or secondary outcome measures. Flexion range however, had a significant positive correlation with kneeling score (r = 0.335, p = 0.010). The kneeling score increased at each time point after surgery and was significantly greater at 12 months than preoperatively (2.7 v 3.5, p = 0.015). The area of sensory loss lateral to the incision was significantly less at 6 and 12 months than at 6 weeks (43.6cm2 and 40.1cm2 v 84.1cm2, p < 0.0001). Conclusion The ability to kneel following cruciate retaining total knee arthroplasty is not affected by the incision position but by time and flexion range. TKA improves the ability to kneel by 12 months post‐surgery. Sensory loss lateral to the incision reduces with time. Level of evidence Therapeutic Level 2.